2021
DOI: 10.3390/pharmaceutics13081283
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Benzothiazole-Based Hsp90 C-Terminal-Domain Inhibitors

Abstract: Heat shock protein 90 (Hsp90) is a chaperone responsible for the maturation of many cancer-related proteins, and is therefore an important target for the design of new anticancer agents. Several Hsp90 N-terminal domain inhibitors have been evaluated in clinical trials, but none have been approved as cancer therapies. This is partly due to induction of the heat shock response, which can be avoided using Hsp90 C-terminal-domain (CTD) inhibition. Several structural features have been shown to be useful in the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Compound 10 was designed using a molecular-dynamics-derived pharmacophore model (Figure S2). 110,111 It was shown to inhibit Hsp90 in the luciferase refolding assay and display antiproliferative activity in the SkBr3 breast cancer cell line (IC 50 = 51 ± 2 μM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compound 10 was designed using a molecular-dynamics-derived pharmacophore model (Figure S2). 110,111 It was shown to inhibit Hsp90 in the luciferase refolding assay and display antiproliferative activity in the SkBr3 breast cancer cell line (IC 50 = 51 ± 2 μM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To date, no HSP90 inhibitor has been approved for cancer therapeutics. The primary obstacles preventing the clinical application of HSP90 inhibitors are the lack of drug‐like properties, organ toxicity, and drug resistance (Dernovšek & Tomašič, 2023). In this study, in vivo experiments showed that PPP exerts no toxicity on the primary organs of mice, thereby suggesting its potential as a natural and safe inhibitor of HSP90.…”
Section: Discussionmentioning
confidence: 99%
“…Representative structures of Hsp90 CTD inhibitors; novobiocin and analogues (1-3) [28,29], deguelin and analogues (4-6) [31,33], silybin (7), EGCG (8) and a benzothiazole-based inhibitor (9) [37].…”
Section: Figurementioning
confidence: 99%
“…Although the potency of Hsp90 CTD inhibitors has improved significantly compared to novobiocin, the scaffold diversity is still scarce. Known inhibitors include novobiocin analogues, analogues of other natural products such as deguelin, EGCG, silybin and scaffolds already established as inhibitors of other targets, e.g., benzothiazole-based DNA gyrase B inhibitors ( 4–9 , Figure 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. To expand the structural diversity of Hsp90 CTD inhibitors, we performed structure-based virtual screening to discover novel scaffolds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation